SACUBITRIL/VALSARTAN: A NEW PARADIGM IN HEART FAILURE - Pai, Sunil; Kamath, Priyanka (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Heart failure (HF) is a syndrome whose cardinal symptoms are dyspnea and fatigue leading to a progressive decrease in exercise capacity. Drugs currently used include angiotensin-converting-enzyme inhibitors, angiotensin receptor blockers (ARB), diuretics, alone or in combination, and in the cases where indicated, digoxin. Sacubitril/valsartan represents a new approach to treatment since the drug complex is made up of moieties of sacubitril, a neprilysin inhibitor and valsartan, an ARB. Since sacubitril and valsartan, inhibit neprilysin and block the angiotensin receptor, respectively, the drug molecule can be considered to play a central role by causing a dual inhibition of both the pathways that play an important role in the pathogenesis of HF. It was approved in July 2015 by the US Food and Drug Administration to reduce the risk of cardiovascular death and hospitalization for HF in patients with chronic HF (NYHA Class II-IV) and reduced ejection fraction. Symptomatic hypotension and angioedema were the major side effects reported from clinical trials. The trials are currently being done to study its effects in HF preserved ejection fraction, chronic kidney disease, and aortic stiffness; the results of which are awaited. Keywords: Sacubitril/valsartan, Neprilysin inhibitor, Dual neutral endopeptidaseneprilysin renin-angiotensin system Inhibition.